The Blood Pressure Lowering Qualities of a Trauma-Focussed Cognitive Behavioural Therapy Approach - Carol Valinejad; Steven Lang (Journal of Basic & Applied Sciences, 2019)
Background: High blood pressure is a serious condition which can make suffers vulnerable to developing conditions such as stroke. Even though research identifies that there can be a link between developing high blood pressure and psychological factors there is little research available to establish how psychological treatment can help sufferers. Instead most of the studies focus on physical interventions and lifestyle changes. Objective: This article aims to share a novel and interesting case example which indicated a potential link between trauma-focussed cognitive behavioural therapy, symptoms of PTSD, and a reduction in high blood pressure. Method: The client was provided with trauma focussed CBT specifically used to target her trauma of an accident which she suffered. The techniques in therapy utilised were, psychoeducation of the therapy model, relaxation therapy, re-living of the trauma, imagery rescripting and systematic desensitization. Following therapy the client recovered from all of her post trauma symptoms and even though her blood pressure was not specifically targeted in treatment, she experienced a corresponding reduction in her blood pressure following treatment. Conclusion: Discussion is centred around how this provides opportunities for researchers to investigate whether there is a causal link between the use of psychological approaches in the reduction in blood pressure level. Further research , for example correlational studies is recommended in this field.